Microbial biobank-based strain phenotyping efficiently identifies plant growth-promoting bacteria from citrus rhizosphere - Hongfei Li; Yuanfa Wang; Lile Deng; Zhiyong Pan (Horticulture Advances)
Abstract Plant growth-promoting rhizobacteria (PGPR) enhance nutrient accessibility and offer disease protection, conferring significant advantages to host plants. Although considerable progress has been made in PGPR research, efficient acquisition of PGPR remains challenging, primarily due to the absence of a microbial biobank, especially for perennial woody crops like citrus. Through 16S rRNA amplicon sequencing, this study analyzed rhizobacterial communities from five citrus-producing regions in China, identifying 9,887 amplicon sequence variants (ASVs) across 28 rhizobacterial phyla. Subsequently, a citrus rhizosphere microbial biobank was established, comprising 3,142 bacterial strains, through extensive isolation of citrus rhizobacteria. From this collection, 269 potential PGPR were screened from 435 bacterial taxa based on their production of indole-3-acetic acid (IAA), siderophore synthesis, phosphate solubilization, and their effects on Arabidopsis root growth. Further evaluation of 22 selected PGPR strains via pot-culture inoculation on citrus and tomato seedlings demonstrated that 11 strains significantly enhanced plant growth. This study provides a foundational theoretical and technological framework for advancing the development and application of beneficial rhizobacteria in citrus agriculture.